Developing a high‐throughput micromilling protocol for evaluating durum wheat milling performance and semolina quality. Issue 5 (24th June 2019) - Wang, Kun; Taylor, Dale; Pozniak, Curtis; Fu, Bin Xiao
Abstract: Background and objectives: Effective and efficient selection of key quality traits is crucial to develop new durum varieties with improved end‐use quality. This study was undertaken to develop a rapid micromilling protocol using a single Brabender Quadrumat Jr. (QJ) semolina mill without purification to predict milling performance and generate semolina for quality analysis. Findings: After grinding 200 g of durum wheat with a QJ mill with the reel sifter removed, the resulting wholemeal was sifted through a laboratory sifter equipped with a bottom screen of 180 µm to remove flour and a top screen of 630 µm to retain bran‐rich fraction. Semolina materials between the two screens were collected. A model for predicting semolina yield ( R 2 = 0.81) was developed based on the amounts of semolina and bran‐rich fraction, thus eliminating the need for additional milling to recover semolina in the bran‐rich fraction. There were highly significant correlations ( r > 0.86) for semolina ash, yellowness, yellow pigment content, protein content, wet gluten, and gluten index between semolina prepared with this proposed protocol and those generated with a Allis‐Chalmers mill. Conclusions: The micromilling protocol developed in this study is rapid and reliable for assessing durum milling performance and for preparing semolina for quality characterization. Significance and novelty: The proposed protocol modified QJ mill and optimized milling conditions. A robust and simplified model was developed for predicting semolina yield with one‐step milling. It is a useful tool for breeding programs or genetic mapping studies that are usually large in sample number but very limited in sample size.